Failed Degradation of JunB Contributes to Overproduction of Type I Collagen and Development of Dermal Fibrosis in Patients With Systemic Sclerosis. Issue 1 (January 2015) - Ponticos, Markella; Papaioannou, Ioannis; Xu, Shiwen; Holmes, Alan M.; Khan, Korsa; Denton, Christopher P.; Bou‐Gharios, George; Abraham, David J.
<x xml:space="preserve">Abstract</x> Objective The excessive deposition of extracellular matrix, including type I collagen, is a key aspect in the pathogenesis of connective tissue diseases such as systemic sclerosis (SSc; scleroderma). To further our understanding of the mechanisms governing the dysregulation of type I collagen production in SSc, we investigated the role of the activator protein 1 (AP‐1) family of transcription factors in regulating COL1A2 transcription. Methods The expression and nuclear localization of AP‐1 family members (c‐Jun, JunB, JunD, Fra‐1, Fra‐2, and c‐Fos) were examined by immunohistochemistry and Western blotting in dermal biopsy specimens and explanted skin fibroblasts from patients with diffuse cutaneous SSc and healthy controls. Gene activation was determined by assessing the interaction of transcription factors with the COL1A2 enhancer using transient transfection of reporter gene constructs, electrophoretic mobility shift assays, chromatin immunoprecipitation analysis, and RNA interference involving knockdown of individual AP‐1 family members. Inhibition of fibroblast mammalian target of rapamycin (mTOR), Akt, and glycogen synthase kinase 3β (GSK‐3β) signaling pathways was achieved using small‐molecule pharmacologic inhibitors. Results Binding of JunB to the COL1A2 enhancer was observed, with its coalescence directed by activation of gene transcription through the proximal promoter. Knockdown of JunB reduced enhancer activation and COL1A2 expression in response to transforming growth factor β. In SSc dermal fibroblasts, increased mTOR/Akt signaling was associated with inactivation of GSK‐3β, leading to blockade of JunB degradation and, thus, constitutively high expression of JunB. Conclusion In patients with SSc, the accumulation of JunB resulting from altered mTOR/Akt signaling and a failure of proteolytic degradation underpins the aberrant overexpression of type I collagen. These findings identify JunB as a potential target for antifibrotic therapy in SSc.